Characterization of pressure-mediated vascular tone in resistance arteries from bile duct-ligated rats - Jadeja, Ravirajsinh N. (Oncotarget, 2017)
In cirrhosis, changes in pressure-mediated vascular tone, a key determinant of systemic vascular resistance (SVR), are unknown. To address this gap in knowledge, we assessed ex vivo dynamics of pressurized mesenteric resistance arteries (diameter ~ 260 μm) from bile duct-ligated (BDL) and sham-operated (SHAM) rats and determined the underlying mechanisms. At isobaric intraluminal pressure (70 mmHg) as well as with step-wise increase in pressure (10-110 mmHg), arteries from SHAM-rats constricted more than BDL-rats, and had reduced luminal area. In both groups, incubation with LNAME (a NOS inhibitor) had no effect on pressure-mediated tone, and expression of NOS isoforms were similar. TEA, which enhances Ca(2+) influx, augmented arterial tone only in SHAM-rats, with minimal effect in those from BDL-rats that was associated with reduced expression of Ca(2+) channel TRPC6. In permeabilized arteries, high-dose Ca(2+) and γGTP enhanced the vascular tone, which remained lower in BDL-rats that was associated with reduced ROCK2 and pMLC expression. Further, compared to SHAM-rats, in BDL-rats, arteries had reduced collagen expression which was associated with increased expression and activity of MMP-9. BDL-rats also had increased plasma reactive oxygen species (ROS). In vascular smooth muscle cells in vitro, peroxynitrite enhanced MMP-9 activity and reduced ROCK2 expression. These data provide evidence that in cirrhosis, pressure-mediated tone is reduced in resistance arteries, and suggest that circulating ROS play a role in reducing Ca(2+) sensitivity and enhancing elasticity to induce arterial adaptations. These findings provide insights into mechanisms underlying attenuated SVR in cirrhosis.